PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN KEPERCAYAAN PELANGGAN TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA RELI BOUTIQUE METRO - Redian Redian (Derivatif : Jurnal Manajemen, 2018)
The aim of this research were to determine the influence of product quality, service quality and trust to customer satisfaction and customer loyalty and customer satisfaction to customer loyalty.  The quantitative approach is implemented in this research. The method of research survey on 100 respondents is taken by purposive sampling (judgment sampling) and questionnaire as an instrument of research. Analysis testing requirements used normality test, homogeneity test, and linearity test with model testing is path analysis. Findings signify that product quality and service quality has no positive and significant effect on customer satisfaction. While on the other hypothesis there is a very significant relationship. This indicates that the customer has not been satisfied with the products and services available and given to the customer. Therefore it is expected Reli Boutique can improve services to customers and maintain the quality of products to be sold to customers. Keywords :   Product quality, service quality, customer trust, customer satisfaction, and customer loyalty.